Relationship between religious coping and post-traumatic stress disorder and professional quality of life of nurses working at COVID-19 wards: a descriptive correlational study - Sanavi Shiri, Zohreh; Tavakoli, Pouran; Momennasab, Marzieh (Frontiers in Public Health, 2025)
PurposeConsidering effects of COVID-19 pandemic on the physical and mental health and professional quality of life (PQoL) of nurses working at COVID-19 wards, it seems necessary to investigate the factors affecting adaptation and reducing adverse effects of this pandemic on nurses. The present study aims to investigate the relationship between religious coping with post-traumatic stress disorder (PTSD) and professional quality of life (PQoL) among nurses.Materials and methodsThis descriptive correlational study was conducted on 368 nurses working at hospitals affiliated to Shiraz University of Medical Sciences. In this research, Mississippi scale for post-traumatic stress disorder (M-PTSD), Pargament’s brief religious coping measure (B-RCOPE) and Stamm’s professional quality of life (proQol) were used for data collection. Statistical significance was considered at p < 0.05.ResultsThe mean score of positive religious coping was 13.01 ± 5.22 (moderate) and the mean score of negative religious coping was 5.27 ± 4.57 (low). The mean PTSD score of nurses was 96.92 ± 18.17 and most of them were at the moderate level (92.9%). The scores of compassion fatigue, secondary traumatic stress, and compassion satisfaction were in the moderate range. The Spearman’s correlation test results showed a significant and negative correlation between positive religious coping and PTSD, and a significant and positive correlation between negative religious coping and PTSD (p = 0.000). Moreover, a significant and positive correlation was observed between compassion satisfaction and positive religious coping (p = 0.005), and a negative and significant correlation was found between compassion fatigue and secondary stress and positive religious coping (p < 0.05). The statistical test of multiple regression revealed a significant correlation between nurses’ positive religious coping and compassion satisfaction, as well as between nurses’ negative religious coping and secondary stress and PTSD (p < 0.05).ConclusionPositive religious coping was correlated with reduced PTSD and improved PQoL among nurses.